Mercurio (Hg) em tartarugas marinhas (Caretta caretta, Chelonia mydas, Eretmochelys imbricata e Lepidochelys olivacea) no Atlântico Sudoeste Tropical e considerações para seu uso em biomonitoramento - Rodríguez, César Augusto Barrios (2023)
With an extensive surface, the oceans are considered the biggest sink of mercury (Hg), where once deposited, it is slowly carried to the depths. As a result, several marine ecosystems are under strong anthropogenic contamination by Hg, resulting in greater exposure of the species that inhabit or use these contaminated areas. Thus, we found high Hg concentrations in species with a long lifespan, such as sea turtles, making these organisms potential biomonitors of Hg in the oceans. In this perspective, the present work aimed to carry out a comparative analysis of Hg concentrations in the carapace of four species of sea turtles (Caretta caretta, Chelonia mydas, Lepidochelys olivacea, and Eretmochelys imbricata) found in the Brazilian coast and that use the Tropical Southwest Atlantic as a major migratory route. Samplings were carried out between 2009 and 2020, at four points in the coastal zone of Brazil (Maranhão, Ceará, Pernambuco, and Bahia). The sampling was carried out mainly from the carapace scutes and, when possible, from other organs, such as the kidney, liver, and muscle. In some cases, all four species' carapace scutes were collected to quantify Hg concentrations and see possible variations between scutes. As an initial part of this study, a review of published studies that quantified Hg concentrations in seven species of sea turtles around the world was carried out. The results showed that more than 80% of the published studies were focused on C. mydas and C. caretta. The North Atlantic and the Mediterranean Sea were the areas that presented the highest number of studies compared to the North Pacific, South Pacific, and South Atlantic. Differences found between regions using C. caretta and C. mydas showed a relationship with the level of environmental contamination. C. mydas is the most studied species and shows an inverse relationship between size and Hg concentrations, associated with ontogenetic diet shifts experienced by this species during growth, which is also discussed in this work. The distribution of Hg in the different areas of the carapace tends to be greater in the vertebral scutes in two species (C. mydas and E. imbricata), suggesting variation in the growth rates of different areas of the carapace, since the vertebral area is the first to develop before costal areas. It was possible to test the use of the carapace as a non-invasive method of biomonitoring, at least for one species (C. mydas). In this species, total Hg and methyl-Hg concentrations decreased with increasing size. Isotopic composition (δ15N and δ13C) did not show a clear relationship with size, suggesting that these turtles would be occupying similar trophic levels and foraging habitats. Mercury concentrations in the carapace correlated positively with concentrations observed in other tissues, confirming its use as a reliable non-invasive method for monitoring internal Hg concentrations, at least in this species of sea turtle. The regional comparison showed that the Hg concentrations in the four species presented a strong relationship with the biological and ecological characteristics of each one, in addition to behaviors such as foraging in deep waters and selectivity for certain types of food items. Finally, this work presents data for four species of sea turtles covering one of the largest coastal zones in the world, so in addition to providing information on the possible influence of biological and ecological characteristics on Hg concentrations, it allowed us to have an idea of the degree of influence activity carried out in four points of the Brazilian coast.